PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SDN 03 MARTAPURA KAB. OKU TIMUR SUMATERA SELATAN - Wagiman,; Sri Rahayu Ningsih, (UNISAN JURNAL, 2024)
This study aims to evaluate the implementation of supervision by the principal in improving the performance of Islamic Education teachers at SDN 03 Martapura, OKU Timur Regency, South Sumatra. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The subjects of this study are the principal and Islamic Education teachers at SDN 03 Martapura. The results show that the supervision conducted by the principal is structured and planned. The supervision includes various aspects, such as direct classroom observations, providing constructive feedback, and offering training and professional development programs for teachers. The principal also facilitates collaboration among teachers to share effective teaching experiences and strategies. The performance of Islamic Education teachers has significantly improved as a result of this supervision. Teachers have become more competent in designing lesson plans, applying innovative teaching methods, and evaluating student learning outcomes. Furthermore, teachers' motivation and commitment to their teaching duties have increased, positively impacting the quality of Islamic education at the school. This study concludes that effective supervision by the principal is a key factor in improving teacher performance. Recommendations are given for the principal to continue enhancing the quality of supervision and providing ongoing support for the professional development of teachers